La Géogouvernance : un concept novateur ? - Michelle Masson Vincent; Nathalie Dubus; Daniel Bley; Christine Voiron; Cécile Helle; Jean-Paul Cheylan; Pierre Douart; Annick Douguedroit; Jean-Paul Ferrier; Frédérique Jacob; Corinne Lampin; Gilles Maignant; et al. (Cybergeo, 2012)
This paper introduces the concept of geogovernance, that differs from governance and from territorial governance, which is a linked concept. It highlights how this new concept is relevant for planning policy respecting sustainable development and how useful it is for building shared projects with inhabitants of a region.